TLR4/NF-κB-mediated M1 macrophage polarization contributes to the promotive effects of ETS2 on ulcerative colitis - Binbin Liu; Jianshun Yu; Jie Zhang; Wei Ye; Jiaming Yao (European Journal of Medical Research)
Abstract Objective ETS2 is a core modulator of macrophages. This study aims to investigate the effects of ETS2 on macrophage polarization in ulcerative colitis (UC) and the involvement of TLR4/NF-κB pathway. Methods A dextran sulfate sodium (DSS)-induced acute UC mice model was established, along with a lipopolysaccharide (LPS)/IFN-γ-stimulated RAW264.7 cell model to mimic inflammation. Immunofluorescence was employed to examine the co-localization of ETS2 with M1 macrophage markers (F4/80 and iNOS). Flow cytometry quantified the iNOS+/F4/80+ M1 macrophage subgroups. Inflammatory cytokine (TNF-α and IL-1β) levels in cell supernatants were detected using enzyme-linked immunosorbent assay. Western blot analyzed the expressions of M1 markers (CD86 and iNOS) and TLR4/NF-κB pathway components (TLR4, p-p65/p65, and p-IκBα/IκBα). An sh-ETS2 lentiviral vector was constructed for ETS2 knockdown in vitro and in vivo. The TLR4 agonist RS 09 was used to rescue macrophage polarization and inflammatory responses. Results In DSS-induced UC mice, ETS2 was significantly upregulated in colon tissues and co-localized with F4/80. LPS/IFN-γ-treated RAW264.7 cells also exhibited elevated ETS2 expression, accompanied by increased inflammatory cytokine secretion, expansion of iNOS+/F4/80+ macrophage subgroups, and activated TLR4/NF-κB pathway. Furthermore, ETS2 deficiency in RAW264.7 cells significantly inhibited the macrophage polarization towards M1 pro-inflammatory phenotype and blocked the TLR4/NF-κB pathway. However, RS 09 counteracted the anti-inflammatory effects of ETS2 knockdown. In vivo silencing of ETS2 attenuated M1 macrophage polarization and inflammatory cytokine production, while ameliorating pathology in UC mice. Conclusion ETS2 enhanced the inflammatory response in UC by activating TLR4/NF-κB-mediated M1 macrophage polarization.